2021
DOI: 10.1590/1413-81232021267.07482021
|View full text |Cite
|
Sign up to set email alerts
|

Sobre risco, violência e gênero: revisão da produção da saúde sobre o sexting entre jovens

Abstract: Resumo Trata-se de uma revisão sistemática acerca da produção do campo da saúde sobre o sexting entre 2009 e 2019. Buscou-se analisar a produção científica com relação ao seu contexto de produção (gênero da primeira autoria, ano da publicação e país de realização), tipo de publicação, área do conhecimento, temas e sujeitos abordados e qual concepção apresentam sobre o sexting. Foram analisadas, durante o segundo semestre de 2019, as 147 publicações disponíveis no PubMed, que tinham o sexting como tema central.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 31 publications
(36 reference statements)
2
1
0
1
Order By: Relevance
“…Despite the observed increasing trend in rape rates perpetrated by all categories of intimate partners and across all age groups, it is notable that the highest percentage of annual growth occurred among cases involving boyfriends/ex-boyfriends and victims aged 15 to 19. These findings underscore the significance of violence within dating relationships, a phenomenon well-documented in other research 33 , 34 , where women are primarily victimized, particularly in cases of sexual and/or physical aggression. It is also important to highlight that this form of violence is increasingly facilitated by technology, such as the dissemination of sexual images and videos without consent 33 , 34 .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Despite the observed increasing trend in rape rates perpetrated by all categories of intimate partners and across all age groups, it is notable that the highest percentage of annual growth occurred among cases involving boyfriends/ex-boyfriends and victims aged 15 to 19. These findings underscore the significance of violence within dating relationships, a phenomenon well-documented in other research 33 , 34 , where women are primarily victimized, particularly in cases of sexual and/or physical aggression. It is also important to highlight that this form of violence is increasingly facilitated by technology, such as the dissemination of sexual images and videos without consent 33 , 34 .…”
Section: Discussionsupporting
confidence: 67%
“…These findings underscore the significance of violence within dating relationships, a phenomenon well-documented in other research 33 , 34 , where women are primarily victimized, particularly in cases of sexual and/or physical aggression. It is also important to highlight that this form of violence is increasingly facilitated by technology, such as the dissemination of sexual images and videos without consent 33 , 34 . A study examining sexual violence notification rates among adolescents revealed a rising trend across all regions of Brazil between 2011 and 2018, with the Northeast exhibiting the lowest rates and percentage variation 35 .…”
Section: Discussionsupporting
confidence: 67%
“…Finally, concerning the approach to this topic, we observe a discursive tone in health-derived productions, associating "sexting" with risk behaviors with STIs, early sexual initiation, and the demand for intervention measures. This production's background is the blame, accountability of young people, and the dictates about exercising sexuality with a strong gender bias 36 . This perspective still permeates the ways of dealing with this issue concerning health care, where digital violence and how subjects face it is rarely discussed.…”
Section: Discussionmentioning
confidence: 99%
“…Finalmente, no que diz respeito à abordagem desse tema, há uma tônica discursiva nas produções oriundas da saúde, associando "sexting" a comportamentos de risco com Infeções Sexualmente Transmissíveis, iniciação sexual precoce e a demanda por medidas de intervenção. Essa produção tem como pano de fundo, a culpabilização, responsabilização dos jovens e ditames sobre o exercício da sexualidade com um forte viés de gênero 36 . Esse olhar ainda impregna as formas de lidar com esse tema no que concerne o cuidado à saúde, onde a violência digital e as formas de seu enfrentamento pelos sujeitos é em geral é pouco discutida.…”
Section: à Guisa De Concluirunclassified